Association between liver fibrosis and thrombotic or bleeding events in acute coronary syndrome patients - Yupeng Liu; Jingjing Song; Wenyao Wang; Kuo Zhang; Jie Yang; Jun Wen; Xiangbin Meng; Jun Gao; Jingjia Wang; Chunli Shao; Yi-Da Tang (Thrombosis Journal, 2022)
Abstract Background The prognostic implication of liver fibrosis in acute coronary syndrome (ACS) patients are scarce. We sought to evaluate whether liver fibrosis scores (LFS) were associated with thrombotic or bleeding events in patients with acute coronary syndrome. Methods We included 6386 ACS patients who underwent percutaneous coronary intervention (PCI). This study determined liver fibrosis with aspartate aminotransferase to platelet ratio index (APRI), aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT ratio), Forns score, and nonalcoholic fatty liver disease fibrosis score (NFS). The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), a composite of all-cause mortality (ACM), myocardial infarction (MI), and ischemic stroke (IS). Results During the follow-up, 259 (4.06%) MACCE and 190 (2.98%) bleeding events were recorded. As a continuous variable or a categorical variable stratified by the literature-based cutoff, LFS was positively associated with MACCE (p > 0.05) but not with bleeding events. Compared with subjects with low APRI scores, AST/ALT ratio scores, Forns scores, and NFS scores, subjects with high scores had a 1.57- to 3.73-fold increase risk of MACCE after adjustment (all p < 0.05). The positive relationship between LFS and MACCE was consistent in different subgroups. Conclusions In ACS patients, increased LFS predicted an elevated risk of thrombotic events but not bleeding. LFS may contribute to thrombotic risk stratification after ACS.